Concentration, distribution and sources of perfluoroalkyl substances and organochlorine pesticides in surface sediments of the northern Bering Sea, Chukchi Sea and adjacent Arctic Ocean. (November 2019) - Kahkashan, Sanober; Wang, Xinhong; Chen, Jianfang; Bai, Youcheng; Ya, Miaolei; Wu, Yuling; Cai, Yizhi; Wang, Siquan; Saleem, Monawwar; Aftab, Javed; Inam, Asif
Abstract: Perfluoroalkyl substances (PFAS) and organochlorine pesticides (OCPs) in surface sediments were investigated from the Bering Sea, the Chukchi Sea and adjacent Arctic Ocean in 2010. Total concentrations (dry weight) of Σ14 PFAS in surface sediments (0.85 ± 0.22 ng g −1 ) of the Bering Sea were lower than that in the Chukchi Sea and adjacent Arctic Ocean (1.27 ± 0.53 ng g −1 ). Perfluoro-butanoic acid (PFBS) and perfluoro-octanoic acid (PFOA) were the dominant PFAS in these areas. The concentrations of Σ15 OCPs in the sediment of the Bering Sea (13.00 ± 6.17 ng g −1 ) was slightly higher than that in the Chukchi and Arctic Ocean (12.05 ± 2.27 ng g −1 ). The most abundant OCPs were hexachlorocyclohexane isomers (HCHs) and dichlorodiphenyltrichloroethane (DDT) and its metabolites. The composition patterns of HCHs and DDTs indicated that they were mainly derived from the early residues via river runoff. Increasing trends of PFAS, HCHs and DDTs in surface sediments from the Bering Sea to the Arctic Ocean were found, indicating oceanic transport. In summary, the concentrations of OCPs were orders of magnitude greater than the observed PFAS concentrations, and the concentrations of PFAS and OCPs in surface sediments from the Bering Sea to the Chukchi Sea and adjacent Arctic Ocean are at the low to moderate levels by comparing with other coastal and marine sediments worldwide. Highlights: PFAS and OCPs were determined in surface sediments of the adjacent Arctic Ocean. OCPs were orders of magnitude greater than the observed PFAS. PFOA was the main compound, and the most abundant OCPs were HCHs and DDTs. Industrial activities may be responsible for high levels of PFAS in the Bering Sea. An increasing latitudinal trend of OCPs were observed.